2003
DOI: 10.1097/00005344-200310000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline Inhibits Smooth Muscle Cell Proliferation, Migration and Neointima Formation after Arterial Injury

Abstract: The tetracyclines are antimicrobials that also inhibit expression of certain matrix metalloproteinases (MMPs). We conducted a series of experiments to determine if minocycline could inhibit MMP expression and limit human aortic smooth muscle cell (SMC) proliferation and migration. Analysis of SMC proliferation was performed after cells were grown in minocycline-incubated media. SMC migration activity was assayed in a micro-Boyden chamber. Western blotting revealed that minocycline reduced SMC production of MMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 26 publications
3
27
0
Order By: Relevance
“…Vena cava and aorta both possess the mechanisms to produce ET-1(1-32), namely expression of functional MMP-2. However, pharmacological inhibition of MMPs by either minocycline [26] or GM6001 did not inhibit big ET-1 induced contraction. These findings suggest that ET-1 (1-32) may not be produced within these blood vessels and have in vivo effects.…”
Section: Et-1 and Mmpsmentioning
confidence: 80%
See 1 more Smart Citation
“…Vena cava and aorta both possess the mechanisms to produce ET-1(1-32), namely expression of functional MMP-2. However, pharmacological inhibition of MMPs by either minocycline [26] or GM6001 did not inhibit big ET-1 induced contraction. These findings suggest that ET-1 (1-32) may not be produced within these blood vessels and have in vivo effects.…”
Section: Et-1 and Mmpsmentioning
confidence: 80%
“…While active MMPs were present in both aorta and vena cava, pharmacological inhibition by the tetracycline antibiotic minocycline (5×10 −5 M) (figure 5B) and GM6001 (5×10 −6 M) did not statistically alter big ET-1 induced contraction in either vessel type. These concentrations of inhibitors were chosen based on previous demonstration of inhibition of MMP2 in arterial tissue (26). Moreover, zymography of aortic homogenates incubated with minocycline prior to and during processing showed a reduction in MMP activity as evidenced by the reduction in intensity of white bands ( Figure 5A, bottom panel).…”
Section: Mmps and Big Et-1 In Aorta And Vena Cavamentioning
confidence: 99%
“…Tetracyclines also may influence the transcriptional or translational process of the MMP synthesis (30 -33). They have been shown to attenuate MMP-2 and -9 activity in the aortic wall (32)(33)(34). Both clinical and animal experimental studies have revealed that tetracyclines decrease serum inflammatory markers and cytokines, as well as MMP in arteriosclerotic diseases (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, a reduction in the number of vascular smooth muscle cells (VSMC) was seen after minocycline treatment, which was attributed to an inhibition of MMP activity and cytokine-induced VSMC migration (Pinney et al, 2003;Yao et al, 2004). Moreover, minocycline has been shown to inhibit VEGFinduced MMP-9 mRNA transcription and protein activation in human aortic VSMCs in vitro (Pinney et al, 2003;Yao et al, 2004). More recently, Shahzad et al (2011) showed minocycline to reduce plaque size and vascular stenosis in diet-induced atherosclerosis through a PARP-1 and p27Kip1-dependent mechanism.…”
Section: Effects Of Minocycline On Atherosclerosismentioning
confidence: 99%
“…Accordingly, minocycline has been shown to protect against diabetic microvascular complications (Krady et al, 2005) and to reduce neointima formation in macrovascular disease following acute vascular injury of the rat carotid artery (Pinney et al, 2003). In these studies, a reduction in the number of vascular smooth muscle cells (VSMC) was seen after minocycline treatment, which was attributed to an inhibition of MMP activity and cytokine-induced VSMC migration (Pinney et al, 2003;Yao et al, 2004). Moreover, minocycline has been shown to inhibit VEGFinduced MMP-9 mRNA transcription and protein activation in human aortic VSMCs in vitro (Pinney et al, 2003;Yao et al, 2004).…”
Section: Effects Of Minocycline On Atherosclerosismentioning
confidence: 99%